Rola i instrumenty controllingu klientów - Żyminkowski, Tomasz (Role and Instruments of Clients' Controlling, 2007)
As part of clients' controlling an enterprise can use a wide spectrum of instruments. They provide both quantitative and qualitative information. They let plan, organize and motivate employees and control strategies and operation programmes which are directed to selected clients of an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 556-562